1998
DOI: 10.1046/j.1523-1747.1998.00312.x
|View full text |Cite
|
Sign up to set email alerts
|

A Possible Vertical Transmission of Human Papillomavirus Genotypes Associated with Epidermodysplasia Verruciformis

Abstract: Epidermodysplasia verruciformis (EV) is characterized by an abnormal genetic susceptibility to a group of related human papillomavirus (HPV) genotypes, including the oncogenic HPV5 and HPV8. The mode of transmission of these viruses remains unknown. In view of the rare incidence of EV, we had a unique opportunity to perform a virologic study of the amniotic fluid and placenta from an EV patient infected with HPV5, HPV8, several other EV HPV, and HPV3. The child was born by cesarean section and the amniotic flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 28 publications
1
41
0
7
Order By: Relevance
“…The authors concluded that the upper 95% confidence interval for detection of perinatal transmission from a woman with evidence of genital HPV was only 2.8%. Recently, Favre et al (1998) found HPV genotypes (HPV types 5, 8, and 24) associated with epidermodysplasia verruciformis (EV) in the amniotic fluid and placenta specimens and cervical scrapes of a mother suffering from EV-induced skin lesions. The child was born by Caesarean section, and the amniotic fluid specimen was taken prior to rupture of membranes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that the upper 95% confidence interval for detection of perinatal transmission from a woman with evidence of genital HPV was only 2.8%. Recently, Favre et al (1998) found HPV genotypes (HPV types 5, 8, and 24) associated with epidermodysplasia verruciformis (EV) in the amniotic fluid and placenta specimens and cervical scrapes of a mother suffering from EV-induced skin lesions. The child was born by Caesarean section, and the amniotic fluid specimen was taken prior to rupture of membranes.…”
mentioning
confidence: 99%
“…The child was born by Caesarean section, and the amniotic fluid specimen was taken prior to rupture of membranes. No viral sequences were detected in peripheral blood mononuclear cells collected two years and six months before Caesarean section, rendering a hematogenous transmission unlikely (Favre et al 1998 Fredericks et al (1993) sampled cervical cells from women 6 wks post partum and buccal smears of their babies for analysis of HPV DNA by PCR. In 73% (8/1 1) of the mother-baby pairs, an identical HPV type was detected in both the buccal mucosa of the newborn and the uterine cervix of the mother.…”
mentioning
confidence: 99%
“…Confirmation of the perinatal transmission of HPV in different mucosa (genital, oral) was subsequently supported by several studies although the route of transmission is not well understood (Syrjänen et al, 2000). Direct maternal transmission during vaginal delivery or at caesarean section following early membrane rupture is possible as well as in utero through semen or ascending infection from mother's genital tract (Syrjänen et al, 2000;Favre et al, 1998). Transplancental transmission is also possible since HPV DNA has been detected by PCR in amniotic fluid of HPV positive pregnant women.…”
Section: Vertical Transmissionmentioning
confidence: 98%
“…[25,27] More rarely, HPVs can be transmitted via perinatal transmission during birth from the mother to child that is also observed in the transmission of other microbial and viral infections. [28,29] Horizontal transmission of HPV is also possible and it was first reported with a 5 year old boy of HPV2 infection presented as warts on the hands and anus of the child via genital-finger transmission. [30] …”
Section: Transmission Of Hpvmentioning
confidence: 99%